Analisis Penerapan Perencanaan untuk Penghematan Beban Pajak PPh Badan Sesuai Undang-Undang No.7 Tahun 2021 pada CV Sukses Mitra Sejahtera - Alvira Zahra Siregar; Syamsul Bahri Arifin (Jurnal Visi Manajemen, 2025)
This study aims to analyze the implementation of tax planning carried out by CV. Sukses Mitra Sejahtera in an effort to reduce the Corporate Income Tax (CIT) burden in accordance with the applicable regulations. The research method used involves communication and observation techniques through direct interviews with relevant parties, data collection, and documentation of related company documents, as well as literature studies and internet media to support the analysis. The data obtained were analyzed using a descriptive qualitative method, focusing on the management of the company’s commercial and fiscal financial statements. The results show that although the company has not fully optimized tax planning implementation, the strategies applied have successfully saved CIT amounting to IDR 3,994,865, or 5.05% of the total tax liability. This demonstrates that applying tax planning in accordance with regulations can provide significant tax savings for the company. The findings also indicate that effective tax planning strategies can reduce tax liabilities legally, while also improving financial management efficiency within the company. Therefore, effective tax planning is crucial in optimizing the company’s tax obligations, supporting business sustainability, and complying with the applicable tax regulations.